Incidence of ancient variants associated with oncological diseases in modern populations. Issue 1 (31st December 2023) - Toncheva, Draga; Marinova, Maria; Borovska, Plamenka; Serbezov, Dimitar
Abstract: Publicly available genome-wide data, sequenced from 2730 ancient human samples were analyzed for genetic predisposition to malignancy. The temporal and spatial incidence of risk variants for cancer diseases in ancient genomes was recorded, allowing for estimates of their frequencies in ancient human communities. We identified 55 risk alleles associated with oncological conditions in the screened ancient samples. For further analysis, we selected three variants conclusively deemed to entail pathogenic effect, the VHL gene's rs28940298, the TP53 gene's rs78378222 and the BRCA2 gene's rs11571833. The contemporary population frequency of these three variants is lower, or similar, to their estimated frequency in ancient human communities, indicating that they might have been subject to negative selection. This is also suggested by their temporal dynamics during the last 10000 years, which show an overall temporal decrease in population frequency. The oldest samples in which these three variants were established testify their ancient origin, including the presence of TP53 gene's rs78378222 variant in 50000 BP old Neanderthal and Denisovan genomes. Our results demonstrate the presence of cancer-causing mutations in ancient human communities and suggest that they differed in frequency among ancient populations as they do among contemporary ones. Data on germline mutations in tumour suppressor genes in ancient human genomes are scarce and their historic prevalence gives insights into the evolution of predisposition to cancer disease and hence helps advance paleogenomic medicine.